2012
DOI: 10.1093/europace/eus062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observations with Closed Loop Stimulation pacemakers in a large patient cohort: the CYLOS routine documentation registry (RECORD)

Abstract: Clinical performance of CLS was very satisfactory in the large cohort studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The Closed Loop Stimulation (CLS) function has been successfully used in patients with vasovagal syncope 5, 6. The CLS algorithm works by monitoring right ventricular impedance, which is thought to be one of the first physiological changes prior to syncope.…”
Section: Introductionmentioning
confidence: 99%
“…The Closed Loop Stimulation (CLS) function has been successfully used in patients with vasovagal syncope 5, 6. The CLS algorithm works by monitoring right ventricular impedance, which is thought to be one of the first physiological changes prior to syncope.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, to date, all 11 studies (observational: five retrospective and two prospective; RCT: three single‐blind and one double‐blind) assessing CLS in VVS have been positive . Also, a previous clinical registry enrolling 706 patients followed during a median of 243 ± 101 days with CLS pacing (implanted due to atrial arrhythmia) has shown that CLS reprogramming was seldom undertaken (<10%) and its deactivation due to intolerance was very low (2.3%) . The ongoing multicenter CLS BIOSync triple‐blind RCT (NCT00292825), enrolling 128 patients with ≥40 years of age and refractory type 2B cardioinhibitory recurrent VVS, may shed some light on the subject of the effectiveness of CLS pacing algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a registry of patients undergoing pacemaker implantation for chronic ventricular pacing [13], 34% of right ventricular leads were deployed at non-apical sites. Similarly, non-apical sites are currently frequently adopted for deployment of the right ventricular lead in patients undergoing implantation of systems for cardiac resynchronization therapy.…”
Section: Rationale For Designmentioning
confidence: 99%
“…Despite the lack of strong evidence in favor of non-apical pacing, and the difficulty in placing [11,12] and accurately classifying [4] the final lead position, pacing at non-apical right ventricular sites has been adopted as a standard procedure at many implanting centers [13].…”
Section: Introductionmentioning
confidence: 99%